COMPARATIVE STUDY OF THE TOXICITY OF SOAP MADE WITH VEGETABLE OIL WASTE - Sena, Marcelo Fonseca Monteiro de; Almeida, Thuanny Moraes de; Silva, Vinícius da Costa; Silva, Elmo Rodrigues da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
One of the safest ways to dispose of residual vegetable oil is delivering this on a collection point for later use in the manufacture of biodiesel or soap. However, it is still superficial the scientific knowledge about the toxic effects of these residual waste vegetable oil and soap on biota. The present study aims to compare, by bioassay with the fish Brachydanio rerio, the median lethal concentration (CL50-72hours) of solid soap produced in IFRJ from residual vegetable oil, with the pasty soap produced from waste vegetable oil and the solid bar soap, both sold in large retail. The fishes were placed in beakers containing eight different concentrations of soap samples. The test consisted of exposure of fishes for 72 hours. The solid soap commercial that uses virgin inputs has significantly lower mortality rate compared to soaps produced from residual vegetable oil, whereas the difference in mortality was insignificant between groups of soaps using residual vegetable oil.